2013
DOI: 10.11139/cj.30.3.371-392
|View full text |Cite
|
Sign up to set email alerts
|

Private Turns: A Student’s Off-screen Behaviors during Synchronous Online Japanese Instruction

Abstract: Although distance language education has been widely adopted in university learning, very few researchers to date have looked at off-screen behaviors of second/foreign language learners in their physical environments while they engage in synchronous (real-time) online courses. This study examined one focal student's off-screen behaviors while she worked in front of the computer in her physical environment during a university-level synchronous Japanese class. The class was mediated by audio-based conferencing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For the basic learning need of "competence", studies found that online learning could help learner achieving learning goals by offering efficient and convenient ways to learn at their own pace (Wilson et al, 2017); enhancing academic attainment (Gilbert, 2015) and developing higher-order thinking through self-regulated learning while integrative learning can increase content knowledge as well as enhance cognitive processing (Ormrod, 2011;Pascarella & Terenzini, 2005). Students were also to become more autonomous (Fotiadou et al, 2017;Suzuki, 2013). With a supportive environment (Baird, 2005) and the benefits of self-paced and selfdirected learning mode (Fotiadou et al, 2017), learners might be positively "aroused" to engage in online learning.…”
Section: Basic Learning Needs and Online Learningmentioning
confidence: 99%
“…For the basic learning need of "competence", studies found that online learning could help learner achieving learning goals by offering efficient and convenient ways to learn at their own pace (Wilson et al, 2017); enhancing academic attainment (Gilbert, 2015) and developing higher-order thinking through self-regulated learning while integrative learning can increase content knowledge as well as enhance cognitive processing (Ormrod, 2011;Pascarella & Terenzini, 2005). Students were also to become more autonomous (Fotiadou et al, 2017;Suzuki, 2013). With a supportive environment (Baird, 2005) and the benefits of self-paced and selfdirected learning mode (Fotiadou et al, 2017), learners might be positively "aroused" to engage in online learning.…”
Section: Basic Learning Needs and Online Learningmentioning
confidence: 99%
“…Aside from these reports that looked at the development and the use of new instructional tools, some studies investigated the actual learning process observed in non-traditional instructional modes. For example, Suzuki (2013) took up a unique approach and examined how off-screen behaviors of a student in an online course would reveal the micro process of learning in this environment. The author discussed a case where a focal learner, Mei, frequently engaged in verbal rehearsal of words, phrases, and sentences in parallel with the ongoing teacher-student sequence when other students were nominated to speak.…”
Section: Research On Japanese Language Teachingmentioning
confidence: 99%
“…"Beyond mere visual observation, initial methods for tracking the location of eye fixation were quite invasive -involving direct mechanical contact with the cornea" (Jacob & Karn, 2003, p. 574). The first non-invasive eyetracking technique was developed by Dodge and Cline around 1901, which could record the light reflected from the cornea (Wade & Tatler, 2011). The main eyetracking techniques were various combinations of corneal reflection and motion pictures before the first head-mounted eye tracker was invented in the late 1940s (Hartridge & Thompson, 1948).…”
Section: Eye-tracking In Reading Researchmentioning
confidence: 99%
“…For example, by studying only output data of chat logs, any information on self-corrections, hesitations, and other learner actions prior to sending off their chat contributions can be lost . By focusing on just the screen, the mouse and the keyboard, we can miss out on all the different scaffolds and support tools that learners use, even if their main focus is interaction via a computer (Suzuki, 2013). Eye-tracking is a useful method to gather data on users engaged in learning with a computer, adding another dimension to the picture that cannot be easily provided by alternative methods, such as video screen capture.…”
Section: Introductionmentioning
confidence: 99%